2010
DOI: 10.2214/ajr.08.1740
|View full text |Cite
|
Sign up to set email alerts
|

Imaging of Soft Tissues Adjacent to Orthopedic Hardware: Comparison of 3-T and 1.5-T MRI

Abstract: Optimizing image acquisition parameters in this phantom model resulted in similar quantitative susceptibility artifact at 3 T and 1.5 T and better qualitative images at 3 T than at 1.5 T.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
44
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 23 publications
3
44
0
Order By: Relevance
“…In order to retain a high-resolution image while at the same time generating smaller geometric distortion artifacts in 3.0 T MRI, we optimized our pulse sequences by increasing the readout bandwidth and reducing the echo time [12,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…In order to retain a high-resolution image while at the same time generating smaller geometric distortion artifacts in 3.0 T MRI, we optimized our pulse sequences by increasing the readout bandwidth and reducing the echo time [12,21,22].…”
Section: Discussionmentioning
confidence: 99%
“…This study demonstrated that VAT and SEMAC-VAT, previously utilized at 1.5 T, 16 can be adapted to 3.0 T with similar success. Farrelly et al 20 found, in a phantom model, reductions in artefact severity with longer readout bandwidths with better overall image quality at 3.0 T. In addition to bandwidth considerations, previous work on improving MRI around metal implants has also focused on VAT techniques originally described by Cho et al 13 Kolind et al 21 also described a VAT SE sequence utilizing high RF and readout bandwidths. This sequence was referred to as a "metal artefact reduction sequence".…”
Section: Discussionmentioning
confidence: 99%
“…Newer developments in implant metal composition and dedicated artefact suppressing MRI sequences have led to a reduction of artefacts [7][8][9][10][11]. Efforts to apply artefact-reducing techniques in a clinical setting have focused on 1.5 T-scanners [12], since it is known that metal artefacts are aggravated with higher field strength [13]. MRI scanners operating at 3 T, however, are increasingly replacing 1.5 T MRIs and create a demand for feasible artefact reduction also at higher field strength.…”
Section: Introductionmentioning
confidence: 99%